1, 3, 5-triacryloylhexahydro-1, 3, 5-triazine improves antibacterial and physicochemical properties of an experimental resin-based cement. (September 2022) - de Oliveira, Naiara Araújo; Leitune, Vicente Castelo Branco; de Souza Balbinot, Gabriela; Guerreiro, Giovan Mateus Balbueno; Wang, Linda; Collares, Fabrício Mezzomo; Sanches Borges, Ana Flávia
Abstract: Stable antibacterial cement could contribute to reducing the biofilm formation for a healthy marginal sealing in high-risk areas in indirect restorations. This study aimed to incorporate 1, 3, 5-triacryloylhexahydro-1, 3, 5-triazine (TAT) on experimental resin-based cements and evaluate its antibacterial and physicochemical properties. An experimental resin-based cement was formulated with 50 wt% Bisphenol A-Glycidyl Methacrylate (BisGMA), 30 wt% Urethane Dimethacrylate (UDMA), 20 wt% Triethylene Glycol Dimethacrylate (TEGDMA), and initiators. Barium silicate glass was used as a filler (45 wt%) and two different groups were tested: CTAT with 15 wt% TAT addition and CCONTROL with no TAT addition. The developed cements were evaluated by their degree of conversion, film thickness, flow, flexural strength, softening solvent, cytotoxicity, and antibacterial activity. Microshear bond strength (μSBS) was evaluated regarding dental tissues, glass-ceramics, and polycrystalline ceramics. CTAT showed a higher degree of conversion, lower cytotoxicity, lower softening solvent, and an increased film thickness when compared to CCONTROL. No statistical difference was found between the groups for flow, flexural strength, planktonic antibacterial analysis, and cytotoxicity. Reduced biofilm formation was observed in the CTAT group. CTAT improved the μSBS values for a polycrystalline ceramic substrate. The addition of 1, 3, 5-triacryloylhexahydro-1, 3, 5-triazine showed anti-biofilm activity, increased degree of conversion, decreased cytotoxicity, and increased bond strength for IPS-YTZP substrate tested.